Artificial intelligence and statistics for quality technology: an introduction to the special issue. Issue 5 (20th October 2021) - Colosimo, Bianca Maria; del Castillo, Enrique; Jones-Farmer, L. Allison; Paynabar, Kamran
Abstract: In many applied and industrial settings, the use of Artificial Intelligence (AI) for quality technology is gaining growing attention. AI refers to the broad set of techniques which replicate human cognitive and analytical skills for problem solving, including Machine Learning, Neural Networks and Deep Learning. This paper presents a brief introduction to the special issue, where AI-based solutions are presented to solve problems that are typically faced in the area of quality technology. Limits and advantages of AI-based solutions are briefly discussed to stimulate creative attention to novel solutions and new directions for future research.